Medial Septum Modulates Cellular Response Induced in Hippocampus on Microinjection of Cholinergic Agonists into Hypothalamic Lateral Supramammillary Nucleus - Ariffin, Mohammed Z.; Low, Chian-Ming; Khanna, Sanjay (Frontiers in Neuroanatomy, 2017)
Cholinergic mechanisms in supramammillary nucleus (SuM), especially the lateral SuM (lSuM) modulates septo-hippocampal neural activity. The lSuM, as compared to the contiguous medial SuM (mSuM) has relatively dense projections to hippocampus and cingulate cortex (Cg). In the present study, we have investigated whether the effects of cholinergic activation of SuM on hippocampal and cortical neural activities involve a cooperative interaction with the medial septum (MS). Microinjection of the broad-spectrum cholinergic agonist, carbachol, or the cholinergic-nicotinic receptor agonist, nicotine, into the lSuM and the mSuM in urethane anesthetized rat evoked a similar pattern of hippocampal theta rhythm. Despite that, only the lSuM microinjections resulted in an increase in expression of c-Fos-like immunoreactivity (c-Fos-ir) in neurons, including interneurons, of the ipsilateral hippocampus with a very dense expression in dentate gyrus. Likewise, a robust induction of c-Fos-ir was also observed in the ipsilateral Cg. Inhibition of the MS with muscimol pre-treatment attenuated both carbachol-evoked c-Fos-ir and theta activation. The findings indicate that cholinergic–nicotinic mechanisms in lSuM evoke not only neural activation via the ascending synchronizing pathway but also an MS-modulated expression of the plasticity-related molecule c-Fos in cortical regions that are strongly innervated by the lSuM.